Gender Preference Among a Sample of Married Women Attending Selected Primary Healthcare Centers in Baghdad Governorate in 2019 - AL- AGELE, Farah Rifaat; Hassan, Batool Ali (Scientific Journal of Medical Research, 2020)
Background: Gender preferences is an important social indicator measuring extent of equity between male and female which reflects underlying socioeconomic and cultural and believes patterns that show a strong preferences for one gender over the other. Objectives: To describe gender preference in married women attending primary health care centers in Baghdad governorate. Methods: A descriptive cross sectional (convenient sample) study had been conducted at Primary Health Care Centers in Baghdad governorate at. AL-Rusafa Health Directorate and AL-Karkh Health, From1st of February to 15th of May2019. Results: Among the 400 study participant The mean age of the study participants was 26.7±5.8 SD,51.8% aged between 25-35 years, About participant family composition desire results showed that less than half of the participant (45.3%) prefer more male child ,43.5% preferred equal number of male and female and only 6.2% preferred female while the remaining 5% has no difference ,Regarding the more effective child gender to the family and community showed that about half of the participant (54%) believed that the male is more effective to the family and community followed by (28%) believed that there was no difference between them and only (18%) said that the female is more effective. Conclusion: Nearly half of the participants exhibit a gender preference for male child , About half of the participants believed that the male is more effective to the family, Almost all participants refuses the idea of intending abortion for undesired fetus.